The role of only-child status in the effect of childhood trauma and parental rearing style on depressive symptoms in Shanghai adolescents - Zhong, Yingyan; Huang, Xinxin; Chen, Jianhua; Li, Yuting; Li, Yan; Chen, Rumeng; Cong, Enzhao; Xu, Yifeng (Frontiers in Psychiatry, 2023)
After decades of the one-child policy, China changed its rules to allow two children in 2016, which altered family dynamics. Few studies have examined the emotional problems and the family environment of multi-child adolescents. This study aims to explore the role of only-child status in the impact of childhood trauma and parental rearing style on depressive symptoms of adolescents in Shanghai, China. A cross-sectional study was conducted on 4576 adolescents (M = 13.42 years, SD = 1.21) from seven middle schools in Shanghai, China. Childhood Trauma Questionnaire-Short Form, the Short Egna Minnen Beträffande Uppfostran, and Children's Depression Inventory were used to evaluate childhood trauma, perceived parental rearing style, and depressive symptoms of adolescents respectively. Results showed that girls and non-only children reported more depressive symptoms, while boys and non-only children perceived more childhood trauma and negative rearing styles. Emotional abuse, emotional neglect, and father’s emotional warmth significantly predicted depressive symptoms in both only children and non-only children. Father's rejection and mother's overprotection were related to adolescents’ depressive symptoms in only-child families, but not non-only child families. Therefore, depressive symptoms, childhood trauma, and perceived negative rearing styles were more prevalent among adolescents in non-only child families, while negative rearing styles were especially associated with depressive symptoms in only children. These findings suggest that parents pay attention to their impacts on only children and give more emotional care to non-only children.